PENGARUH PENYULUHAN TERHADAP PENGEMBANGAN KAPULAGA DI HUTAN RAKYAT: KASUS DI KABUPATEN CIAMIS DAN TASIKMALAYA, JAWA BARAT - Dian Diniyati; Budiman Achmad (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
Recently, cardamom crops in Ciamis and Tasikmalaya Districts are getting popular among private forest farmers. However, the cultivation technique of  cardamom mostly was not in accordance with the guidance of  cardamom planting.  Therefore, their management need to be improved, alter natively by extension. This research aimed to identify the change of  farmer knowledge on cardamom cultivation in private forests. This research was conducted from June to December 2013 in Kalijaya Village, Banjarsari Subdistrict, Ciamis District and Karyabakti Village, Parung ponteng Subdistrict, Tasikmalaya District. Total respondens consist of  60 private forest farmers who were randomly selected. The implemented research design was using pre-test and post-test group design. The scores of  pre-test and post-test were examined using paired sample t-Test at 95% confident level. The result showed that the extension through lecture and discussion methods on cardamom development in private forests were evidently effective to improve the farmers knowledge. This was proved by the score of  post-test was higher compare to the pre-test score, from 13.3% to 60% in Kalijaya Village, and from 10% to 66.67% in KaryabaktiVillage. Therefore, for the empowerment and to change the social of  the farmers, the extension using lecture and discussion methods should be carried on.